Багатосекційні резонансні інвертори напруги в електронному пуско-регулювальному апараті - Лупенко, А.М. (Технічна електродинаміка, 2012)
The voltage resonant inverter with parallel connection of arbitrary numbers of half bridge sections as electronic ballast output stage for high pressure sodium lamps is analyzed. The analytical expressions for n-sections inverter currents and powers are obtained, the features of its power phase control are considered